Exculpating Injustice: Coroner Constructions of White Innocence in the Postbellum South. (January 2021) - Gaby, Sarah; Cunningham, David; Lee, Hedwig; Ward, Geoff; Jackson, Ashley N.
Research notes the broad complicity of white public officials in historical racial violence and repression. These discussions emphasize the role of criminal justice actors in perpetrating and enabling this repression. Extending this assessment, the authors examine coroners' facilitation of white racial dominance through administrative performances constructing white innocence. Using cases from post-Emancipation South Carolina, the authors document race-related patterns of exculpatory effort, through the omission and curation of evidence amid the post-Reconstruction rise of white supremacist redemption. The authors theorize that these exculpatory efforts helped sustain an ideology of white innocence and institutional legitimacy by constructing a white "law-abiding" public. The authors argue that such coroner misconduct not only degrades the rule of law but has broader implications, including its corruption of the corpus of mortality and crime data. Finally, the authors suggest that these administrative performances persist in present-day coroner reporting, including in the exculpation of racist police violence.